Analysis of carbon footprint during cnc turning by using life cycle assessment method - Chim, Cheing Han (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Cutting fluids and method of lubrication systems play important role in manufacturing industries. However, usage of cutting fluids have contaminated enviroment and being environmentally disposal which accounted for approximately 17% of total production cost. Some eco-friendly machining methods, such as MQL machining and dry machining method, have been developed instead of traditional flooding method.